Ruta montana L. from Morocco: comprehensive phytochemical analysis and exploration of its antioxidant, antimicrobial, anti-inflammatory and analgesic properties - El Ouardi, Mohamed; Drioiche, Aziz; Tagnaout, Imane; Benouahi, Aicha; AL kamaly, Omkulthom; Shahat, Abdelaaty Abdelaziz; Fadoua, El Makhoukhi; Nadia, Handaq; Sahpaz, Sevser; Zair, Touriya; Belghiti, Mohamed Alaoui (Frontiers in Chemistry, 2025)
Ruta montana L., a medicinal plant native to Morocco's Middle Atlas region, has been traditionally used for its therapeutic properties. This study aims to investigate its phytochemical composition and evaluate its biological and pharmacological activities, with a focus on its essential oil (EO) and phenolic extracts. The essential oil was extracted via hydrodistillation and analyzed using GC-MS to determine its chemical composition. Aqueous, hydro-ethanolic, and hydro-methanolic extracts were prepared and analyzed for their polyphenol, flavonoid, and tannin content using spectrophotometric methods and HPLC/UV ESI-MS. Antimicrobial activity was assessed using minimum inhibitory concentration (MIC) assays, while antioxidant potential was evaluated using the DPPH radical scavenging method. Analgesic and anti-inflammatory effects were tested using abdominal writhing and edema inhibition models, respectively. Subacute toxicity was assessed by monitoring organ weights and biochemical parameters in treated animals. The EO was predominantly composed of 2-undecanone (81.16%) and decyl propanoate (9.33%). Phenolic extracts were rich in rosmarinic acid 3′-glucoside, p-coumaroylquinic acid, quercitrin, ferulic acid, and embelin. The EO exhibited strong antimicrobial activity (MIC = 2.34–37.5 mg/mL), particularly against Aspergillus niger, and significant analgesic effects (44.55% reduction in abdominal writhing at 0.2 mL), outperforming the aqueous extract (23.37%). Phenolic extracts demonstrated notable antioxidant activity (IC50 = 117.24 μg/mL in DPPH), while the EO showed moderate antioxidant potential (IC50 = 29.42 μg/mL; BHT = 1.62 μg/mL). Anti-inflammatory assays revealed that both the EO (71% inhibition at 0.2 mL) and aqueous extract (79% inhibition at 300 mg/kg) were comparable to indomethacin. Subacute toxicity tests indicated no significant organ weight changes, although slight increases in hepatic AST (91.33 U/L) and creatinine (2.36 mg/L) were observed at higher doses. These findings highlight R. montana's potential as a natural source of antioxidant, antimicrobial, and anti-inflammatory agents. The EO, in particular, shows promise as a therapeutic alternative. However, further studies are needed to evaluate its long-term safety and efficacy. R. montana demonstrates significant pharmacological potential, particularly its essential oil, which warrants further investigation for therapeutic applications.